Development of A Hybrid Method by Integrating Electrocoagulation Countinous System with Activated Charcoal Adsorption to Treat Sago Wastewater - Amelia Puspitasari; Sutanto Sutanto; Linda Jati Kusumawadani (Universitas Pakuan, 2022)
Wastewater from the sago industry can pose a risk of pollution because it contains chemicals such as high organic matter content, fiber, 4% unextracted starch, nitrogen solution, and cyanoglucoside which are difficult to degrade in the environment. Sago wastewater is generally acidic, has foul smells, and has a high solids concentration. In this study, a hybrid method using electrocoagulation continuous system and activated carbon adsorption was developed to decrease organic and inorganic contaminates which considered importand environmental concern. These two methods have the advantages of simple equipment, easy operation, low efficiency, and short reaction time. The flow rate will affect the pause time of the sample in the reactor. The longer the pause time, feeding will lead to an increase in the level of turbidity that can be lowered. Industrial wastewater variations in the initial analysis then carried out the electrocoagulation process in a continuous system with a container capacity of 1680 mL with an electrode distance of 2 cm, a voltage of 18 volts, and wastewater into a container with a flow rate of 1 mL/, 2 mL/second, 3 mL/ sec, 4 mL/sec, and 5 mL/sec. In addition, the waste is directly into a container containing charcoal. The parameters studied were COD, BOD, TSS, TDS, KMnO4, DO, pH, DHL, and Al concentration analysis with Atomic Absorption Spectrophotometer, odor, and color analysis. The maximum removal efficiency for TDS, TSS. COD, BOD, TDS, KMnO4 were 81.16%, 87.58%, 91.32%, 48.66%, 99.07%, for a flow rate of 1 mL/second, also other parameters also met have met the quality standards set by PerMenLH No. 5.